ABOUT STABILITY IN THE SYSTEMS WITH IMPULSES - Гургула, Степан Іванович; Собкович, Роман Іванович (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2019)
With the help of Liapunov’s secondary method were issued criteries of stability, asymptotic stability and non-stability of simple solution of the elementary system of differential equations with impulsive action in the fixed moments of time.